Examining recent trends in the racial disparity gap in tap water consumption: NHANES 2011–2018. Issue 2 (11th February 2022) - Rosinger, Asher Y; Patel, Anisha I; Weaks, Francesca
Abstract: Objective: As tap water distrust has grown in the USA with greater levels among Black and Hispanic households, we aimed to examine recent trends in not drinking tap water including the period covering the US Flint Water Crisis and racial/ethnic disparities in these trends. Design: Cross-sectional analysis. We used log-binomial regressions and marginal predicted probabilities to examine US nationally representative trends in tap and bottled water consumption overall and by race/ethnicity. Setting: The National Health and Nutrition Examination Survey data, 2011–2018. Participants: Nationally representative sample of 9439 children aged 2–19 years and 17 268 adults. Results: Among US children and adults, respectively, in 2017–2018 there was a 63 % (adjusted prevalence ratio (PR): 1·63, 95 % CI (1·25, 2·12), P < 0·001)) and 40 % (PR: 1·40, 95 % CI (1·16, 1·69), P = 0·001)) higher prevalence of not drinking tap water compared to 2013–2014 (pre-Flint Water Crisis). For Black children and adults, the probability of not drinking tap water increased significantly from 18·1 % (95 % CI (13·4, 22·8)) and 24·6 % (95 % CI (20·7, 28·4)) in 2013–2014 to 29·3 % (95 % CI (23·5, 35·1)) and 34·5 % (95 % CI (29·4, 39·6)) in 2017–2018. Among Hispanic children and adults, not drinking tap water increased significantly from 24·5 % (95 % CI (19·4, 29·6)) and 27·1 % (95 % CI (23·0, 31·2)) in 2013–2014 to 39·7 % (95 % CI (32·7, 46·8)) and 38·1 % (95 % CI (33·0, 43·1)) in 2017–2018. No significant increases were observed among Asian or White persons between 2013–2014 and 2017–2018. Similar trends were found in bottled water consumption. Conclusions: This study found persistent disparities in the tap water consumption gap from 2011 to 2018. Black and Hispanics' probability of not drinking tap water increased following the Flint Water Crisis.